(untitled) (Carte Romanze, 2019)
The essay reflects on the modes of the ottava rima of Giovanni Boccaccio’s Filostrato: the narrative and the lyric one. The lyricism inside the poem distinguishes it from the 14th century “cantari”, which appear only narrative works. This also applies to the metrical and formal differences between Boccaccio’s ottava and the “ottava canterina”.